If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 11 = 3x + 151 Reorder the terms: 11 + 13x = 3x + 151 Reorder the terms: 11 + 13x = 151 + 3x Solving 11 + 13x = 151 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 11 + 13x + -3x = 151 + 3x + -3x Combine like terms: 13x + -3x = 10x 11 + 10x = 151 + 3x + -3x Combine like terms: 3x + -3x = 0 11 + 10x = 151 + 0 11 + 10x = 151 Add '-11' to each side of the equation. 11 + -11 + 10x = 151 + -11 Combine like terms: 11 + -11 = 0 0 + 10x = 151 + -11 10x = 151 + -11 Combine like terms: 151 + -11 = 140 10x = 140 Divide each side by '10'. x = 14 Simplifying x = 14
| x^2+9x+y^2-9y=13 | | 3(5x-2)-4(10-x)=-(6+x) | | 3p^3=81 | | 3(w-9)=9 | | 2x^3=3x^2 | | 3x^2-39x+120=0 | | x(x+24)=58 | | .15=30(9-.15) | | 9x=45x+7 | | 6.4c-8=c+13.6 | | x^2-8x-a= | | 15x-17=-x+7 | | x-(-12)=-2 | | x^2-6x-a= | | 2m^2-5m^2-12m=0 | | x-(-5)=-23 | | y^2-3y-28= | | 1.33333333x+4=1.5x+2 | | 5(y+3)+9=3(y-2)+8 | | -4-5x=11-10 | | 12-4x=8x+24 | | 28+w=35 | | (k-6)(k-1)=k-2 | | x^2+4x+a= | | y=8x^2-8 | | 3(x-4)-4=-3x+6x-21 | | 3x^3-12x^2+8x-1=0 | | a^2-14a+45=0 | | 3(x-4)-4=-3+6x-21 | | -3+-6x+-9x^2=0 | | 7x-3x=-20 | | x+6+-1x+4=10+-1x |